Contributions of African Researchers to Trends, Trajectory and Development of Priming Theory - Kehinde Abdul-afees Ayantunji (The Journal of Studies in Language, Culture and Society)
Priming is a theoretical paradigm that has dominated media effects studies worldwide, with important studies testing and building the theory. There is an arguable age-long discourse of intellectual poverty on theory building and theory testing in Africa, an exposition that follows the arguable domination of the global South by the global North in contributions to research and theory on communication and media studies, especially the priming theory. This study re-examines this discourse by determining the trajectory, trends and development of the theory, showcasing the contributions of scholars from the two divides to priming paradigm. The study adopted desk review and quantitative content-analysis of studies as its methodology. Findings show that most of the studies on priming were conducted between 2011-2020 and 2001-2010 in the USA with Nigeria coming behind Kenya.The studies focused attention on mass media and mostly adopted probability and quantitative methodology. Findings show that studies that adopted priming from Africa lacked the capacity to contribute to theory building and testing, because of gaps in methodology and application. The study recommended capacity building on theory testing and theory building for African communication researchers to bridge the gap.